Re-Expression of ERα and AR in Receptor Negative Endocrine Cancers via GSK3 Inhibition - Sharma, Vikas; Joshi, Jayadev; Yeh, I-Ju; Doughman, YongQiu; Blankenberg, Daniel; Wald, David; Montano, Monica M. (Frontiers in Oncology, 2022)
DNA methylation, catalyzed by DNA methyltransferase (DNMT), is a well-characterized epigenetic modification in cancer cells. In particular, promoter hypermethylation of AR and ESR1 results in loss of expression on Androgen Receptor (AR) and Estrogen Receptor (ER), respectively, and is associated with a hormone refractory state. We now report that Glycogen Synthase Kinase 3 (GSK3) phosphorylates DNMT1 at S714, which is localized to a 62 amino acid region referred to as auto-inhibitory linker, which functions to occlude the DNA from the active site of DNMT1 to prevent the methylation of unmethylated DNA. Molecular Dynamics simulation indicates that phosphorylation at S714 resulted in conformational rearrangement of the autoinhibitory domain that inactivated its ability to block the methylation of unmethylated DNA and resulted in enhanced DNA binding. Treatment with a novel and more selective inhibitor of GSK3 resulted in decreased methylation of the promoter region of genes encoding the Androgen Receptor (AR) and Estrogen Receptor alpha (ER) and re-expression of the AR and ER in AR negative prostate cancer and ER negative breast cancer cells, respectively. As a result, concurrent treatment with the GSK3 inhibitor resulted in responsiveness of AR negative prostate cancer and ER negative breast cancer cells to inhibitors of the AR or ER, respectively, in in vitro and in vivo experimental models.